Epidemiology and outcome of acute kidney injury in hospitalized children: experience from a tertiary care hospital in Eastern India - Sen, Anirban; Bhattacharjee, Koushik; Kanti Das, Mrinal; Pal, Atanu; Dasgupta, Sanjay; Bandyopadhyay, Arunansu (International Journal of Contemporary Pediatrics, 2023)
Background: The aim of the study was to assess the etiology, clinical profile and short-term outcome of acute kidney injury in hospitalized children. Methods: A single centre prospective observational study conducted at a tertiary care hospital in eastern India. Consecutive hospitalized children aged between one month to twelve years who developed AKI according to AKIN criteria were included in the study. Relevant clinical and laboratory parameters as guide by clinical condition along with outcome of patients were recorded at the time of discharge and at one month and three months after discharge. Results: 116 hospitalized children who developed AKI were included in the study; 63 (54.3%) participants are above 5 years of age with male to female ratio of the study population was 1.07:1. Infections (46.5%), acute glomerulonephritis (19.8%), snake bite (11.2%) and post-surgery (8.6%) were the common causes of AKI. 43.1% of them had AKIN stage 3. 66.4% had oliguria, 33.6% had shock. 72.4% required admission at Pediatric Intensive Care Unit support, 32.4% required ionotrop support, 44.8% required mechaicanical ventilator support. Around 65% requrired dialysis support; of which 75% recieved hemodialysis and 25% requied peritoneal hemodialysis. Mortality rate was 44%. At discharge, 41.6% (n=27) of the patients had complete renal recovery from AKI. Percentage of partial renal recovery at the time of discharge, 1 month and 3 months after discharge were respectively 53.8%; 47.7% and 10%. 3 patients at the time of discharge and 2 patients after 3 months required persistent dialysis support. Number of factors are associated with poor outcome especially higher acute kidney injury state, critically ill patients and low serum albumin at admission. Conclusions: Infection is the leading cause of acute kidney injury in hospitalized children in this part of world. Mortality in critically ill children with acute kidney injury is high. Various clinical parameters at presentation are associated with poor short term renal outcome.